Impact of donor lung quality on post‐transplant recipient outcome in the Lung Allocation Score era in Eurotransplant – a historical prospective study. (13th February 2020) - Smits, Jacqueline M.; Gottlieb, Jens; Verschuuren, Erik; Evrard, Patrick; Hoek, Rogier; Knoop, Christiane; Lang, György; Kwakkel‐van Erp, Johanna M.; Vos, Robin; Verleden, Geert; Rondelet, Benoit; Hoefer, Daniel; et al.
Summary: The aim of this study was to investigate whether there is an impact of donation rates on the quality of lungs used for transplantation and whether donor lung quality affects post‐transplant outcome in the current Lung Allocation Score era. All consecutive adult LTx performed in Eurotransplant (ET) between January 2012 and December 2016 were included ( N = 3053). Donors used for LTx in countries with high donation rate were younger (42% vs. 33% ≤45 years, P < 0.0001), were less often smokers (35% vs. 46%, P < 0.0001), had more often clear chest X‐rays (82% vs. 72%, P < 0.0001), had better donor oxygenation ratios (20% vs. 26% with PaO2 /FiO2 ≤ 300 mmHg, P < 0.0001), and had better lung donor score values (LDS; 28% vs. 17% with LDS = 6, P < 0.0001) compared with donors used for LTx in countries with low donation rate. Survival rates for the groups LDS = 6 and ≥7 at 5 years were 69.7% and 60.9% ( P = 0.007). Lung donor quality significantly impacts on long‐term patient survival. Countries with a low donation rate are more oriented to using donor lungs with a lesser quality compared to countries with a high donation rate. Instead of further stretching donor eligibility criteria, the full potential of the donor pool should be realized.